1998
DOI: 10.1016/s0009-9236(98)90120-5
|View full text |Cite
|
Sign up to set email alerts
|

The effects of relative timing of sirolimus and cyclosporine microemulsion formulation coadministration on the pharmacokinetics of each agent*

Abstract: This study shows that the relative timing of administration of cyclosporine and sirolimus significantly affects the blood concentrations of sirolimus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
52
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(55 citation statements)
references
References 15 publications
3
52
0
Order By: Relevance
“…Furthermore, coadministration of oral cyclosporine with oral sirolimus in healthy volunteers resulted in a 6-fold increase in the C max and a 2.5-fold increase in the area under the concentration verus time curve for sirolimus (Rapamune product information; Wyeth-Ayerst). A similar study performed in stable kidney transplant patients found that the C max was significantly increased and the T max was reduced when cyclosporine was given concomitantly with sirolimus compared with cyclosporine dosing 4 h after the sirolimus dose (Kaplan et al, 1998). This interaction was most likely due to altered bioavailability because a change in T max was observed and the increase in C max was much greater than the change in the sirolimus trough levels.…”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, coadministration of oral cyclosporine with oral sirolimus in healthy volunteers resulted in a 6-fold increase in the C max and a 2.5-fold increase in the area under the concentration verus time curve for sirolimus (Rapamune product information; Wyeth-Ayerst). A similar study performed in stable kidney transplant patients found that the C max was significantly increased and the T max was reduced when cyclosporine was given concomitantly with sirolimus compared with cyclosporine dosing 4 h after the sirolimus dose (Kaplan et al, 1998). This interaction was most likely due to altered bioavailability because a change in T max was observed and the increase in C max was much greater than the change in the sirolimus trough levels.…”
Section: Discussionmentioning
confidence: 86%
“…A pharmacokinetic interaction has already been reported between calcineurin inhibitors and sirolimus (Kaplan et al, 1998;Cattaneo et al, 2004). Its mechanism mainly involves inhibition of the CYP 3A isoenzymes and, to a minor extent, inhibition of P-glycoprotein (Wacher et al, 2002;Cummins et al, 2004).…”
Section: Metabolism Of Sirolimus By Cyp 3a4 and Cyp 3a5mentioning
confidence: 99%
“…This can lead to pharmacokinetic interactions, as initially described in rats (Stepkowski et al, 1996). In renal transplant patients, coadministration of the two drugs resulted in increased sirolimus area under the concentration curve (1.45-fold), through concentration (1.49-fold) and maximal concentration (1.72-fold), compared with staggered administration, with no significant consequence on cyclosporine exposure (Kaplan et al, 1998). This interaction mainly involves CYP 3A inhibition as demonstrated in rats (Wacher et al, 2002) as well as in vitro using CYP 3A4-transfected Caco-2 cells (Cummins et al, 2004).…”
mentioning
confidence: 90%
“…The wide interpatient variability of sirolimus is largely attributed to the effects of intestinal cytochrome p450 3A enzymes (CYP3A) and P-glycoprotein activity on sirolimus absorption [16]. The coadministration of sirolimus and cyclosporine in renal transplant patients alters the bioavailability of sirolimus, increasing both the C max and area under the concentration-time curve (AUC) of sirolimus [28]. Sirolimus absorption was also shown to be reduced by the intake of a high-fat meal, although a 35% increase in AUC was reported [29].…”
Section: Pharmacokinetic Propertiesmentioning
confidence: 99%